Present and future shortwave radiative forcing of tire and brake wear microplastics - Kylling, Arve; Evangeliou, Nikolaos; Eckhardt, Sabine; Stohl, Andreas (Zenodo, 2022)
We present for the first time the present and future shortwave (SW) instantaneous radiative forcing (IRF) due to tire and brake wear particles (TBWPs). We include the effects of both airborne and deposited TBWP. The latter is important for snow covered surfaces. This may be particularly important for the polar regions that, according to the latest AMAP (Arctic Monitoring and Assessment Programme) report, warm three times more quickly than the rest of the planet, and faster than previously thought. To the best of our knowledge, the optical properties, and an accurate size distribution for TBWPs are currently lacking. However, by assuming an upper limit of the absorbing properties of TBWPs (equal to black carbon), we present the first estimates of the radiative forcing of TBWPs. We also make sensitivity test with different assumptions regarding TBWP absorptivity and size distributions to calculate the effect and uncertainty our assumptions have in the overall results. Finally, we quantify the future SW IRF of TBWPs until 2100 globally and for various regions due to forecasted changes in TBWP emissions, surface concentrations and deposition rates.